The Role of Preachers in Building Ukhuwah Islamiyah Youth in Belawan I, Medan City - Muktarruddin; M.Rifky Azhar Hasibuan; Sri Tsulatsiah Putri Nabila Ginting; Vira Nabila (MAQOLAT: Journal of Islamic Studies, 2023)
Youth is a valuable asset in community development, including in the context of ukhuwah Islamiyah. Building ukhuwah Islamiyah among youth requires collaborative efforts from various parties, and preachers have an important role in this effort. This research discusses the role of preachers in building youth Islamic ukhuwah in Belawan I, Medan city. This research was conducted with the aim of understanding how Islamic preachers can contribute to building strong, mutually supportive relationships and strengthening bonds between young Muslims. The research method used in this study is a qualitative research with a descriptive-analytical approach. Data were collected through in-depth interviews with preachers who were actively involved in da'wah activities and youth development in the Belawan I environment. The results of the interviews were analyzed to identify the specific role of the preachers in building youth ukhuwah Islamiyah. Based on the results of the research that has been done, the Da'i's role in enhancing Ukhuwah Islamiyah in the Belawan I neighborhood of Medan city has been successful with the Da'i opportunity to convey da'wah to the community so that the Da'i is able to change the mindset of the community towards Ukhuwah Islamiyah and is able to apply good attitudes among brothers and sisters.